2011
DOI: 10.1021/ic2002095
|View full text |Cite
|
Sign up to set email alerts
|

m-Carborane-Based Chiral NBN Pincer-Metal Complexes: Synthesis, Structure, and Application in Asymmetric Catalysis

Abstract: We have succeeded in synthesizing m-carborane-based chiral NBN-pincer ligands, 1,7-bis(oxazolinyl)-1,7-dicarba-closo-dodecaborane (Carbox) (7-9). The combination of bis(hydroxyamides) and 3 equiv of diethylaminosulfur trifluoride (DAST) is a key step for cyclization to form oxazoline rings in excellent yields. X-ray crystal structures of these ligands confirmed three donor sites, one central B and two flanking N atoms in fixed positions. The electrophilic halogenation of the Carbox pincer ligands with iodine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…79 Similar to the report of Mirkin, the m-carborane 73 was initially dilithiated, but in this case, the dilithiation was followed by a treatment with carbon dioxide and a quenching with protons to give the corresponding carborane-dicarboxylic acid 80. After the conversion of the carboxyl group into the acid chloride 81, reaction with a chiral aminoalcohol ensured the formation of carborane bis(amide)s 82a82c.…”
Section: Carborane-based Pincer Ligands With a Meridional Coordinatiomentioning
confidence: 83%
“…79 Similar to the report of Mirkin, the m-carborane 73 was initially dilithiated, but in this case, the dilithiation was followed by a treatment with carbon dioxide and a quenching with protons to give the corresponding carborane-dicarboxylic acid 80. After the conversion of the carboxyl group into the acid chloride 81, reaction with a chiral aminoalcohol ensured the formation of carborane bis(amide)s 82a82c.…”
Section: Carborane-based Pincer Ligands With a Meridional Coordinatiomentioning
confidence: 83%
“…The 1 H and 13 1073-1057 cm -1 ) [43], indicating that intracluster bonding was not perturbed by functionalization of the icosahedron.…”
Section: [Scheme 5]mentioning
confidence: 93%
“…It was found that an exchange coupling for both Fe III atoms in 31 was strongly antiferromagnetic. [58]. Chiral rhodium complexes 32 (chloride form) and 35 (acetate form) were found to be an effective catalyst (1 mol%) for asymmetric conjugate reaction of α,β-unsaturated esters, giving both a high enantiomeric excess (93%-94% ee).…”
Section: Ironmentioning
confidence: 97%
“…Reaction of o-carboranylmethyl ammonium salt with commercially available phenyl aldehyde provided the phenyl(carboranylmethyl)imine 12 (Chart 2 and Scheme 3) in good yield [57]. Another interesting series of compounds is that of chiral bis(oxazolilnyl)-m-carboranes 13-14 that were synthesized via a multistep synthesis [58]. Briefly, m-carborane dicarboxylic acid was transformed to the acyl chloride with SOCl 2 and further condensed with two equivalents of the corresponding resolved amino alcohols to provide the uncycled bis(hydroxyamide)-m-carborane intermediates.…”
Section: Complexes Of Monosubstituted 1-4 and 12mentioning
confidence: 99%